2011
DOI: 10.1080/03235408.2010.484947
|View full text |Cite
|
Sign up to set email alerts
|

Potential of ochratoxin A production byAspergillus carbonariusstrains isolated from grapes at different ecological factors

Abstract: Aspergillus carbonarius is known to colonize and produce ochratoxin A (OTA) on grapes and its derived products which is harmful to humans. We screened and tested A. carbonarius strains which isolated from grapes for production of OTA and selected three high OTA producing strains (ACSP1, ACSP2, ACSP3) for this study. These strains were further tested for their ability to produce OTA at different ecological factors [temperature 15, 25, 30, 358C; water activity (a w ) 0.98, 0.95, 0.90, 0.88; and pH 4.0, 7.0, 9.0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
4
1
0
Order By: Relevance
“…Our results are in good agreement with previous works reporting 30 C and 0.960e0.985 a w as optimum conditions of temperature and water activity, respectively, in the absence of antifungal agents (Mitchell et al, 2004;Tassou et al, 2007;Patharajan et al, 2011). Moreover, our findings are in line with Lasram et al (2010) who reported a significant decrease of A. carbonarius growth when temperature increased over 37 C. Pateraki et al (2007) after assessing the germination of five A. carbonarius strains under different a w levels and NaMBS Fig.…”
Section: Fungal Growthsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in good agreement with previous works reporting 30 C and 0.960e0.985 a w as optimum conditions of temperature and water activity, respectively, in the absence of antifungal agents (Mitchell et al, 2004;Tassou et al, 2007;Patharajan et al, 2011). Moreover, our findings are in line with Lasram et al (2010) who reported a significant decrease of A. carbonarius growth when temperature increased over 37 C. Pateraki et al (2007) after assessing the germination of five A. carbonarius strains under different a w levels and NaMBS Fig.…”
Section: Fungal Growthsupporting
confidence: 92%
“…Moreover, Astoreca et al (2007) reported that the highest OTA amounts were measured at 30 C/0.99 a w when assessing two A. carbonarius strains isolated from dried grapes. The highest levels of OTA were found at 0.98 a w and decreased when a w decreased as reported by other researchers as well (Mitchell et al, 2004;Bellí et al, 2005;Medina et al, 2007;Lasram et al, 2010;Patharajan et al, 2011). After treatment with NaMBS, results showed that OTA content was enhanced even in the cases where fungal growth was delayed by the presence of the antifungal agent.…”
Section: Ota Accumulationsupporting
confidence: 75%
“…Our results are in good agreement with previous works reporting 30 °C and 0.960-0.985 a w as optimum conditions of temperature and water activity, respectively, in the absence of antifungal agents (Mitchell et al, 2004;Tassou et al, 2007b;Patharajan et al, 2011). Moreover, our findings are in line with Lasram et al (2010) who reported a significant decrease of A. carbonarius growth when temperature increased over 37 °C.…”
Section: Fungal Growthsupporting
confidence: 93%
“…at 30 °C/0.99 a w when assessing two A. carbonarius strains isolated from dried grapes. The highest levels of OTA were found at 0.98 a w and decreased when a w decreased as reported by other researchers as well (Mitchell et al, 2004;Bellí et al, 2005b;Medina et al, 2007a;Lasram et al, 2010;Patharajan et al, 2011).…”
Section: Ota Accumulationsupporting
confidence: 81%
See 1 more Smart Citation